2012
DOI: 10.1002/ijc.27453
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of cysteine cathepsins and cystatins in human gliomas

Abstract: Cysteine cathepsins play an important role in shaping the highly infiltrative growth pattern of human gliomas. We have previously demonstrated that the activity of cysteine cathepsins is elevated in invasive glioblastoma (GBM) cells in vitro, in part due to attenuation of their endogenous inhibitors, the cystatins. To investigate this relationship in vivo, we established U87-MG xenografts in non-obese diabetic (NOD)/severe combined immunodeficiency (SCID)-enhanced green fluorescent protein (eGFP) mice. Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 39 publications
1
45
0
2
Order By: Relevance
“…Recently, Sun et al [43] showed increased expression of stefin B in the nucleus of T98G astrocytoma cells that was associated with delay in cell cycle progression and stefin B was also found to inactivate caspase-3/7 in the nucleus. On the other hand, Gole et al [44] reported that expression of stefin B is decreased in invading GBM cells and at the periphery of the tumor in orthotopic xenografts of GBM in nude mice indicating differential expression of stefin B in different subpopulations of GBM cells within a tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Sun et al [43] showed increased expression of stefin B in the nucleus of T98G astrocytoma cells that was associated with delay in cell cycle progression and stefin B was also found to inactivate caspase-3/7 in the nucleus. On the other hand, Gole et al [44] reported that expression of stefin B is decreased in invading GBM cells and at the periphery of the tumor in orthotopic xenografts of GBM in nude mice indicating differential expression of stefin B in different subpopulations of GBM cells within a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine cathepsins have been extensively investigated in glioma by our research groups [4], [6], [8], [41], [44], [48] and by others [3], [10]. CatB, CatL and CatS have been reported to be associated with glioma progression, and are highly overexpressed at mRNA, protein and activity levels in GBM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…À l'intérieur même d'une sous-population tumorale, les cellules présentent de façon hétérogène des altérations moléculaires, telles que l'amplification de l'EGFR (points oranges), de la MET (points jaunes), du PDGFR (points verts) ou la méthylation du promoteur de MGMT (points bleus). B. Les différentes sous-populations tumorales expriment des gènes différents en faveur d'un comportement biologique différent [19][20][21][22][23][24][25][26][27][28][29] (voir Glossaire pour définition des abréviations).…”
Section: Hétérogénéité Intratumoraleunclassified
“…GFAP et pERK [20] Nestine et pAKT [20] ASPHD2, NFE2L2, LAMC1, CD133 [24] ET-1, IL-8 [26] CD133 [19] IGFBP2 et vimentine [21] Autotaxine, éphrine B3, Bcl-w, PTK 2 [21] Hif1, IL-8 [25] E-sélectine [27] Nestine [28] Stéphine B [22] Cathepsines S et L [22] Gènes de la voie Notch [29] …”
Section: Cellules Initiatrices De Gliome (I)unclassified